Chronic exposure to cafeteria-style diet in rats alters sweet taste preference and reduces motivation for, but not 'liking' of sucrose. (1st January 2022) - Fam, Justine; Clemens, Kelly J.; Westbrook, R. Fred; Morris, Margaret J.; Kendig, Michael D.
Abstract: Obesity is associated with changes to taste perception and brain reward circuitry. It is important to understand how these effects alter the preference for palatable foods and drinks, given that these are widely consumed, and leading risk factors for obesity. This study examined the effects of diet-induced obesity on sweet taste preference by analysing the microstructure of licking for sugar solutions and assessing pERK expression in the nucleus accumbens shell and insula. Adult male Sprague-Dawley rats were fed standard chow (Control; n = 16) or a varied, palatable cafeteria diet (Caf; n = 16) for 12 weeks. Two-choice preference tests between 2%, 8% and 32% sucrose solutions were conducted at baseline and in weeks 11–12 of the diet. Rats in the Caf group trebled energy intake and doubled weight gain relative to controls. In tests held under water restriction after 11 weeks of diet, the Control group reliably preferred higher sucrose concentrations (i.e., 32% > 8% > 2%). Relative to controls, the Caf group showed a stronger preference for 32% vs. 2% sucrose, lower preference for 32% vs. 8% sucrose, and were indifferent to 8% vs. 2% sucrose. Testing without water restriction increased preference for higher sucrose concentrations in both groups. Chronic Caf diet increased the latency to lick, decreased total licks and reduced alternations between spouts, but did not alter lick cluster size, a measure of hedonic appraisal, on any test. Following a final exposure to a novel sucrose concentration, neuronal activity (pERK) in the insula and nucleus accumbens shell was significantly reduced in the Caf group. Results indicate that differences in 'liking' do not underlie obesity-induced changes to sweet taste preference.